‘Omics’ and Plant Responses to Botrytis cinerea - AbuQamar, Synan F.; Moustafa, Khaled; Tran, Lam-Son P. (Frontiers in Plant Science, 2016)
Botrytis cinerea is a dangerous plant pathogenic fungus with wide host ranges. This aggressive pathogen uses multiple weapons to invade and cause serious damages on its host plants. The continuing efforts of how to solve the “puzzle” of the multigenic nature of B. cinerea’s pathogenesis and plant defense mechanisms against the disease caused by this mold, the integration of omic approaches, including genomics, transcriptomics, proteomics and metabolomics, along with functional analysis could be a potential solution. Omic studies will provide a foundation for development of genetic manipulation and breeding programs that will eventually lead to crop improvement and protection. In this mini-review, we will highlight the current progresses in research in plant stress responses to B. cinerea using high-throughput omic technologies. We also discuss the opportunities that omic technologies can provide to research on B. cinerea-plant interactions as an example showing the impacts of omics on agricultural research.